Islamic Education Centers in Mosque-Based Communities - Dariyanto, Dariyanto (Academia Publication, 2024)
This study aimed to describe the programs and their implementation in the mosque as a community education center, using a qualitative approach with a case study at the H.M. Wijadi Dandangan Mosque in Kediri City. The findings showed that the mosque functioned as a center for Islamic education through three main programs: a spiritual education program (tahsin for mothers, Pengajian Ahad Pagi Haromain, kuliah shubuh, thematic routine study, khataman, and tabligh akbar), a skill education program (English Massive, screen printing and graphic design courses, adhan and iqomah courses), and a social education program (Jumat Berkah). The Tahsin Women’s Program had been running for about five years, held from Monday to Thursday between 12:30 p.m. and 2:30 p.m. using the sorogan method, fostering social bonds and Qur’anic values. The English Massive program, also running for five years, was conducted every Thursday and Saturday using teacher-centered and pairing methods. The Jumat Berkah program was held routinely every Friday. However, several challenges were identified, including a lack of interest from new students in the tahsin program, inconsistent participation, limited awareness of the mosque due to its new status, age-related learning difficulties, and fluctuating motivation and engagement among learners.